Design Study of a Miniaturized Multi-layered Antenna-in-package for 2.4 GHZ Wireless Communication - Jalal Naghar; Otman Aghzout; Azzeddin Naghar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper proposes a novel miniaturization technique to enhance the radiation properties of small multi-layer patch antenna used in packaged circuits. The multilayered antenna design is composed of three layers with different shapes. An enhancement on the radiation properties has been obtained by optimizing the geometry of the radiated element and the parasitic conductor of the middle layer. The whole design has been implemented on the FR4 substrate with dielectric constant of 4.4, thickness of 1.6 mm and Copper thickness of 5 μm. The first layer is a driven element while second and the third layer are parasitic patch elements. The optimized multilayer antenna has a very small size of 12×6×5 mm^3. Considering the small size of the antenna, a detailed study of the parameter affecting the radiation has been considered to force the antenna to operate at 2.4 GHz band. Miniaturization techniques based on the current distribution have been also taken into account to shift down the resonant frequency and reduces more and more the antenna size at the designed operating frequency. The miniaturized antenna maintains performant radiation characteristics in terms of reflexion coefficient, bandwidth and directivity. All developed antennas are simulated using the commercial Electromagnetic CST Microwave Studio software. Achieved results demonstrate a good performance with low cost and compact size.